The Effectiveness of Temperature and Heat Module Through P2F to Improve Science and Numeracy Literacy - Muhammad Arifuddin; Ernita Desi Fitriani; Andi Ichsan Mahardika (Universitas Papua, Jurusan Pendidikan Fisika FKIP Unipa, 2026)
This study aims to enhance students skills in science literacy and numeracy by creating temperature and heat modules using the learning of physics modeling at least in the effective category. This module is designed as a learning innovation because students frequently struggle to grasp the concepts of temperature and heat conventional methods. This study used the ADDIE development model and Research and Development (R&D) research methods to conduct trials on 35 grade XI students from high schools in Banjarmasin. The ADDIE model was chosen because it has clear stages for needs analysis, design, development, implementation, and evaluation, allowing the resulting modules to be systematically tested. The trial was carried out using a one-group pre-test post-test design. Data was collected through the (THB), which has been adjusted to numeracy and science literacy indicators. The results showed that this module was effective, with an n-gain score of 0.74, which shows how much students' skills improved after using it. Therefore, the temperature and heat modules learned through physics modeling can be used to improve students' numeracy and literacy skills. They can also be used as an innovative alternative learning resource in high school.